Accuracy of a fecal immunochemical test according to outside temperature and travel time - Niedermaier, Tobias; Hoffmeister, Michael; Brenner, Hermann (Clinical epidemiology, 2018)
Background: Fecal immunochemical tests (FITs) are widely used and recommended for colorectal cancer (CRC) screening. Fecal hemoglobin (Hb) may degrade with long transport durations and high ambient temperatures, potentially reducing sensitivity to detect CRC and its precursors. This study aimed at investigating the impact of temperatures and sample travel times on diagnostic performance of a quantitative FIT for detection of advanced neoplasms (AN, CRC, or advanced adenoma). - Methods: Participants of screening colonoscopy in south-western Germany conducted a quantitative FIT prior to bowel preparation between February 2012 and June 2016. From available locations and dates of stool sampling and transport, maximum ambient temperatures were linked to 2,870 participants aged 50-79 years and sample return durations were recorded. The impact of ambient temperatures and return duration on FIT sensitivity and specificity was assessed for five different cutoffs between 10 and 25 µg Hb/g feces. - Results: At a positivity threshold of 20 µg Hb/g feces, overall sensitivity and specificity for detecting any AN were 40% (95% CI, 35-47%) and 95% (95% CI, 94-96%), respectively. Inverse associations between maximum ambient temperature (median 18.1°C, inter-quartile range [IQR] =11.4-24.9°C) and sensitivity of FIT were observed which were stronger at higher cutoffs. Sample return durations (median 6 days, IQR =4-8 days) were not associated with variable sensitivities or specificities. - Conclusion: Hb degredation during fecal sample transportation in summer months may be of some concern for diagnostic performance of the FIT evaluated under routine conditions in a middle-European climate.
Gesehen am 14.11.2018